2021
DOI: 10.1017/s1368980021001014
|View full text |Cite
|
Sign up to set email alerts
|

Food security mediates the decrease in women’s depressive symptoms in a participatory nutrition-sensitive agroecology intervention in rural Tanzania

Abstract: Objective: To investigate if food security mediated the impact of a nutrition-sensitive agroecology intervention on women’s depressive symptoms. Design: We used annual longitudinal data (4 time points) from a cluster-randomized effectiveness trial of a participatory nutrition-sensitive agroecology intervention, the Singida Nutrition and Agroecology Project (SNAP-Tz). Structural equation modelling estimation of total, natural direct, and natural indirect effects was used to investigate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 87 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…A total of two articles addressed the Singida Nutrition and Agroecology Project, which taught agroecology methods designed to increase food diversity and food security among smallholder families in Tanzania through increasing biodiversity and increasing the cultivation of legumes [ 140 , 141 ]. A cluster-randomized efficacy trial demonstrated that levels of probable depression, as measured by the Center for Epidemiologic Studies Depression Scale (CES-D), decreased by 43% among women farmers in the intervention group [ 140 ]. Structural equation modelling revealed that the increase in house food security explained 23% of this impact [ 141 ].…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of two articles addressed the Singida Nutrition and Agroecology Project, which taught agroecology methods designed to increase food diversity and food security among smallholder families in Tanzania through increasing biodiversity and increasing the cultivation of legumes [ 140 , 141 ]. A cluster-randomized efficacy trial demonstrated that levels of probable depression, as measured by the Center for Epidemiologic Studies Depression Scale (CES-D), decreased by 43% among women farmers in the intervention group [ 140 ]. Structural equation modelling revealed that the increase in house food security explained 23% of this impact [ 141 ].…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…Much of the literature addressed multiple interventions or multi-component interventions, proscribing evaluation of specific mechanisms. Only one intervention was of the gold-standard experimental design, and its narrow target of food-insecure female farmers with young children in Tanzania limits generalizability to other farming populations [ 140 , 141 ]. The most consistent methodology used was self-report questionnaires concerning mental health literacy programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation